Predictors of Informal Health Payments: The Example from Turkey - Ozgen, H. (2012)
Little is known about the factors that can affect informal health payments in Turkey, which is pertinent given that Turkey has been undergoing and considering a series of reforms in the health sector. This paper aims to examine the predictors of informal payments in Turkey. The study surveyed a random sample of 3,727 people in a medium-sized city, of whom 706 received medical care for illness and/or non-illness related reasons, using a Turkey-specific version of a model questionnaire focused exclusively on informal out-of-pocket payments. Using multivariable logistic model, household health expenditure, health insurance, service type and provider ownership were found to be statistically significant predictors of informal payment. The findings suggest the supply side factors as the main drivers of informal payments and thus a need for radical changes in the supply side as well as actions to rebuild lost confidence in the health care system of Turkey.